2007
DOI: 10.1016/j.jclinepi.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Parents were accurate proxy reporters of urgent pediatric asthma health services—a retrospective agreement analysis

Abstract: Objective-To assess agreement between parents' proxy reports of children's respiratory-related health service use and administrative data.Study Design and Setting-A retrospective analysis of statistical agreement between clinical and claims data for reports of physician visits, emergency department (ED) visits, and hospitalizations in 545 asthmatic children recruited from sites in the greater Toronto area was conducted. Health services use data were extracted from the Ontario Health Insurance Plan and Canadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 28 publications
4
26
1
Order By: Relevance
“…All of the data were self-or parent proxy-reported, and accuracy was therefore dependent upon participant recall. Reports of health services by parent proxy respondents in this study showed good to excellent agreement with administrative data (Ungar, Davidson-Grimwood, & Cousins, 2007). The study sample represented a broad urban and suburban population of children with asthma.…”
Section: Discussionsupporting
confidence: 62%
“…All of the data were self-or parent proxy-reported, and accuracy was therefore dependent upon participant recall. Reports of health services by parent proxy respondents in this study showed good to excellent agreement with administrative data (Ungar, Davidson-Grimwood, & Cousins, 2007). The study sample represented a broad urban and suburban population of children with asthma.…”
Section: Discussionsupporting
confidence: 62%
“…In an assessment of recall validity, the parents in this study were found to be highly reliable reporters of prestudy ED visits and hospital admissions. 42 This study did not directly assess the effect of medication adherence on exacerbation; however, the interview data contained detailed information on other potential confounders, unavailable in administrative data. The results regarding the effects of out-of-pocket expenditures on exacerbations are difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Bhandari and Wagner [2] reported a weighted average of 60% agreement at 3 months recall, 36% agreement at 6 months recall, and 20% agreement at 12 months recall. Finally, the type of HCRU reported can also affect the level of agreement, with self-report accuracy increasing with more rare or memorable visits, including inpatient hospitalizations or visits to a specialist [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have evaluated the validity of parent proxyreported utilization data, existing studies have found that parental reporting of HCRU data for children correlates well with medical records [10,16,18,19]. These studies used in-person and telephone interviews and focused on parental recall for conditionspecific utilization [16,19] or for service-specific utilization [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation